WABAH PENYAKIT DAN PENCEGAHANNYA PERSPEKTIF BUYA HAMKA DAN IBN KATSIR STUDI KOMPARATIF DALAM TAFSIR AL-AZHAR DAN TAFSIR AL-QUR’AN AL-ADZIM - fauzi; Abdul Muiz (AL-BAYAN INSTITUTE, 2024)
This article discusses Buya Hamka's perspective on disease and its prevention efforts based on the interpretation of several verses of the Qur'an, and compares it with Ibn Katsir's interpretation. The main focus of the study is the interpretation of Q.S. Al-Anbiya' verse 83 about the story of the Prophet Ayyub who suffered from illness, Q.S. An-Nahl verse 69 about the benefits of honey as medicine, and Q.S. Al-Maidah verse 6 which is related to ablution as a form of personal hygiene. Buya Hamka interprets that the illness that afflicted the Prophet Ayyub came from the interference of the devil, although this interpretation does not have a strong sanad. In disease prevention, Hamka emphasized the importance of honey which has been recognized traditionally and medically as having properties as an antibacterial and natural healer. In addition, ablution is also associated with health benefits, especially in preventing infectious diseases. This article also reviews the similarities and differences in interpretation of Buya Hamka and Ibn Katsir. Both agreed that honey and ablution have health value, but differed in interpreting the origin of the Prophet Ayyub's disease. This study shows that the spiritual values in the Qur'an can make an important contribution to the understanding of physical health and its prevention